Technological Developments in Education and Automation - Iskander, Magued; Kapila, Vikram; Karim, Mohammad A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Technological Developments in Education and Automation includes a set of rigorously reviewed world-class manuscripts dealing with the increasing role of technology in daily lives including education and industrial automation. Technological Developments in Education and Automation contains papers presented at the International Conference on Industrial Electronics, Technology & Automation and the International Conference on Engineering Education, Instructional Technology, Assessment, and E-learning which were part of the International Joint Conferences on Computer, Information and Systems Sciences and Engineering Topics Covered: Online-Learning including development of courses and systems for engineering, technical and liberal studies programs; online laboratories; intelligent testing using fuzzy logic; taxonomy of e-courses; and evaluation of online courses in comparison to traditional courses. Pedagogy including benchmarking; group-learning; active learning; teaching of multiple subjects together; ontology; and knowledge management. Instruction Technology including internet textbooks; virtual reality labs, instructional design, virtual models, pedagogy-oriented markup languages; graphic design possibilities; open source classroom management software; automatic email response systems; tablet-pcs; personalization using web mining technology; intelligent digital chalkboards; virtual room concepts for cooperative scientific work; and network technologies, management, and architecture. Engineering and Technical Education including course design; assessment, virtual laboratories; robotics; and web enhanced courses Robotics, Control Systems and Automation: Advanced and Distributed Control Systems, Automation, Expert Systems, Robotics, Factory Automation, Intelligent Control Systems, Man Machine Interaction, Manufacturing Information System, Motion Control, and Process Automation. Vision Systems: for human action sensing, face recognition, and image processing algorithms for smoothing of high speed motion, Electronics and Power Systems: Actuators, Electro-Mechanical Systems, High Frequency Converters, Industrial Electronics, Motors and Drives, Power Converters, Power Devices and Components, and Power Electronics
Keywords: Education; Software engineering; Electronics; Education; Educational Technology; Electronics and Microelectronics, Instrumentation; Software Engineering/Programming and Operating Systems